Comparative transient expression analyses on two conserved effectors of Colletotrichum orbiculare reveal their distinct cell death‐inducing activities between Nicotiana benthamiana and melon. (16th June 2021) - Chen, Jinlian; Inoue, Yoshihiro; Kumakura, Naoyoshi; Mise, Kazuyuki; Shirasu, Ken; Takano, Yoshitaka
Abstract: Colletotrichum orbiculare infects cucurbits, such as cucumber and melon ( Cucumis melo ), as well as the model Solanaceae plant Nicotiana benthamiana, by secreting an arsenal of effectors that suppress the immunity of these distinct plants. Two conserved effectors of C . orbiculare, called NLP1 and NIS1, induce cell death responses in N . benthamiana, but it is unclear whether they exhibit the same activity in Cucurbitaceae plants. In this study, we established a new Agrobacterium ‐mediated transient expression system to investigate the cell death‐inducing activity of NLP1 and NIS1 in melon. NLP1 strongly induced cell death in melon but, in contrast to the effects seen in N . benthamiana, mutations either in the heptapeptide motif or in the putative glycosylinositol phosphorylceramide‐binding site did not cancel its cell death‐inducing activity in melon. Furthermore, NLP1 lacking the signal peptide caused cell death in melon but not in N . benthamiana . Study of the transient expression of NIS1 also revealed that, unlike in N . benthamiana, NIS1 did not induce cell death in melon. In contrast, NIS1 suppressed flg22‐induced reactive oxygen species generation in melon, as seen in N . benthamiana . These findings indicate distinct cell death‐inducing activities of NLP1 and NIS1 in these two plant species that C . orbiculare infects. Abstract : Agrobacterium ‐mediated transient expression analyses on two fungal conserved effectors, NLP1 and NIS1, reveal their distinct cell death‐inducing activities between Nicotiana benthamiana and melon.